Observation in Lembaga Pembinaan Khusus Anak (LPKA) Class II Palangka Raya City - Apriatama, Dony; Makdalena, Makdalena; Rahmaniah, Rahmaniah; Stevandy, Matias; Yeriana, Yeriana; Oktarina, Angela; Rusvini, Rusvini (ASEAN Journal of Empowering Community, 2022)
Observation's purpose and compliance include knowing the implementation of education guidance, stature, coaching, and guidance of child client services in LPKA class II Palangka Raya, understanding the supporting factors and obstacles to implementing guidance in LPKA class II Palangka Raya. The benefits for students open students' insights about guidance services, care, education, and coaching in non-education institutions, namely LPKA class II Palangka Raya. Provide an overview of the service provided in LPKA class II palangka raya. Provide understanding for students that the prospects for tutoring and counseling work are not only limited to educational settings but can also be in other institutions. Benefits for the study program Established cooperation between LPKA class II Palangka Raya with Guidance and Counseling Program of Universitas Palangka Raya. Benefits for LPKA Human Resource Assistance. Exchange of information for an institution.